PARP Inhibitors for Metastatic CRPC: More Answers than Questions, a Systematic Review and Meta-Analysis - Ray Manneh; Javier Molina-Cerrillo; Guillermo de Velasco; Linda Ibatá; Susan Martínez; Álvaro Ruiz-Granados; Teresa Alonso-Gordoa (Pharmaceuticals)
PARP inhibitors (PARPi), alone or in combination with androgen receptor signaling inhibitors (ARSi), have shown clinical benefit in metastatic castration-resistant prostate cancer (mCRPC), particularly in tumors with homologous recombination repair (HRR) gene alterations. Recent data from the TALAPRO-2 trial complete the current evidence on PARPi–ARSi combination strategies in this setting. Background/Objectives: To evaluate the efficacy and safety of PARPi-based therapies—monotherapy and combination with ARSi—in patients with mCRPC, focusing on molecular subgroups defined by DNA repair alterations. Methods: We conducted a systematic review and meta-analysis of phase III randomized controlled trials (RCTs) assessing PARPi as monotherapy or in combination with ARSi. Searches were performed in PubMed, EMBASE, the Cochrane Library, and oncology conference proceedings up to February 2025. Outcomes included radiographic progression-free survival (rPFS), overall survival (OS), second progression-free survival (PFS2), and grade ≥3 adverse events (AEs). Data were pooled using a random-effects model, with subgroup analyses by DNA repair status. Results: Five RCTs (n = 2921) were I confirmincluded: three on combination therapy (n = 2271) and two on monotherapy (n = 650). Combination therapy improved rPFS in the ITT (HR = 0.64; 95% CI: 0.56–0.74), HRRm (HR = 0.55; 95% CI: 0.44–0.68), and BRCAm (HR = 0.33; 95% CI: 0.18–0.58) subgroups. OS was also improved in the ITT (HR = 0.80; 95% CI: 0.70–0.92), HRRm (HR = 0.68; 95% CI: 0.55–0.83), and BRCAm (HR = 0.54; 95% CI: 0.34–0.85) groups. No benefit was observed in non-HRRm patients. PFS2 favored combination therapy (HR = 0.77; 95% CI: 0.64–0.91). Grade ≥3 AEs were more frequent (RR = 1.44; 95% CI: 1.20–1.73). Monotherapy improved rPFS in ITT (HR = 0.46; 95% CI: 0.20–0.81) and BRCAm (HR = 0.33; 95% CI: 0.15–0.75); OS benefit was seen only in BRCAm (HR = 0.73; 95% CI: 0.57–0.95). Conclusions: PARPi therapies improve outcomes mainly in HRR- and BRCA-mutated mCRPC. Molecular selection is key to optimizing benefit and minimizing toxicity. Further research on the activity of PARPi combinations in non-HRR mutated mCRPC is needed to better understand the underlying mechanisms of efficacy.